2020
DOI: 10.1016/j.envres.2019.108805
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and legacy brominated flame retardants in the breast milk of first time Irish mothers suggest positive response to restrictions on use of HBCDD and Penta- and Octa-BDE formulations

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 28 publications
3
15
2
Order By: Relevance
“…The study population, approach to recruitment, sampling, and sample pooling are reported in detail in Wemken et al [16] , 2020. In brief, study recruitment and sampling protocols, adhered (with minor deviations) to WHO UNEP guidelines for developing a national protocol for measurement of POPs in human milk [13] and the study protocols of Pratt et al [15] , 2012. Comparability of study design with the study of Pratt et al [15] ( Mothers were recruited while attending breastfeeding clinics in two Irish maternity hospitals, who also participated in the Pratt et al [15] , 2012, namely University Hospital Galway (UHG) and the Coombe Women and Infants University Hospital (Coombe), Dublin.…”
Section: Human Milk Sample Collection and Poolingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population, approach to recruitment, sampling, and sample pooling are reported in detail in Wemken et al [16] , 2020. In brief, study recruitment and sampling protocols, adhered (with minor deviations) to WHO UNEP guidelines for developing a national protocol for measurement of POPs in human milk [13] and the study protocols of Pratt et al [15] , 2012. Comparability of study design with the study of Pratt et al [15] ( Mothers were recruited while attending breastfeeding clinics in two Irish maternity hospitals, who also participated in the Pratt et al [15] , 2012, namely University Hospital Galway (UHG) and the Coombe Women and Infants University Hospital (Coombe), Dublin.…”
Section: Human Milk Sample Collection and Poolingmentioning
confidence: 99%
“…Prior to this study, the most recent study of PCDD/Fs and PCBs in Irish human milk was based on samples collected in 2010 [15] . Measured concentrations were compared to results from Irish human milk samples included in the third WHO survey that were collected in 2002 [12] .…”
Section: Introductionmentioning
confidence: 99%
“…A problem that arises for some chemicals is how to handle samples with values below the LOQ. In the past, values below the LOQ have been assigned the ½ X LOQ 47,48 or LOQ√2 46,49 . However, assigning a value to a large number of samples with values below the LOQ may not provide an accurate estimate of the true population mean concentration.…”
Section: Technological Advancesmentioning
confidence: 99%
“…These FRs dominated the polymer industry in the past, but recently, their application became closely monitored, and it is regulated in many countries due to their toxicity, persistence, and bioaccumulation issues. For instance, the study conducted by Wemken et al (2020) discovered the presence of different brominated FRs in the breast milk of first-time mothers living in Ireland [ 16 ]. Another work reported the high levels of brominated compounds found in the urban soils from the city of Melbourne, Australia [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a positive response to the regulatory rules applied to this class of FRs is evident. For example, the ban on the use of hexabromocyclododecane (HBCD) and penta-bromodiphenyl ether (BDE) resulted in the lower concentrations of these compounds detected in the breast milk [ 16 ].…”
Section: Introductionmentioning
confidence: 99%